Validation of multicolor imaging signatures of central serous chorioretinopathy lesions vis-a-vis conventional color fundus photographs - Kumar Saurabh (Indian Journal of Ophthalmology, 2020)
Purpose: The current study compares the ability of multicolor imaging (MCI) to detect the lesions of central serous chorioretinopathy against conventional color fundus photographs (CFP). Methods: It was a retrospective, observational case series of 93 eyes of 58 patients of central serous chorioretinopathy who underwent MCI and CFP. MCI and spectral-domain optical coherence tomography (SD-OCT) were performed using Spectralis SD-OCT system (HRA + OCT). CFP was obtained using FF 450 Plus fundus camera (Carl Zeiss Meditec, Jena, Germany). SD-OCT was considered gold standard for subretinal fluid (SRF) and retinal pigment epithelium detachment (PED). CFP was considered confirmatory investigation for fibrin and blue autofluorescence image (BAF) was considered gold standard to detect retinal pigment epithelium (RPE) atrophy. Results: CFP could detect SRF in 41 (44.1%) eyes. MCI detected SRF in 43 (46.2%) eyes. The sensitivity and specificity of MCI to detect SRF were 70.7% and 94.3%, respectively. PED was detected by CFP in 21 (22.6%) eyes and MCI in 27 (29%) eyes. The sensitivity and specificity of MCI to detect PED were 70% and 97.7% respectively. CFP could pick RPE atrophy in 52 (55.9%) eyes whereas MCI was picked it in 78 (83.9%) of eyes. Conclusion: Both MCI and CFP were inferior to a gold standard in identifying the SRF, PED, and RPE atrophy. However, MCI was better than CFP in comparison with gold standard for these clinical findings in CSC. Thus, MCI seems to be a more valuable imaging tool compared to CFP.